Stimulus size matters: Do life-sized stimuli induce stronger embodiment effects in mental rotation? - Kaltner, Sandra; Jansen, Petra; Riecke, Bernhard E. (Journal of Cognitive Psychology, 2017)
Against the background of the embodied cognition approach this experiment investigated the influence of motor expertise on object-based vs. egocentric transformations in a chronometric mental rotation (MR) task using images of either the own or another person’s body as stimulus material. The present study aimed to clarify two issues: (1) whether stimulus size (life size vs. small) is able to induce embodiment effects and (2) which role self-awareness processes play when using stimuli of the own body. The same design was conducted twice using both small stimuli (Study 1) and life-size human figures (Study 2). Using life-sized figures in Study 2 resulted in an explicit advantage of self-related stimuli and improved performance for motor experts compared to non-motor experts in both object-based and egocentric transformations. In conclusion, these results suggest that life-sized figures do indeed induce stronger embodiment effects in MR.
Keywords: Riecke; Riecke_2017; bernhard-riecke; journalPaper; mental rotation; petra-jansen; sandra-kaltner